PENGARUH MODEL PEMBELAJARAN SYNECTICS DIPADU MIND MAPS TERHADAP KEMAMPUAN BERPIKIR KREATIF, SIKAP KREATIF, DAN PENGUASAAN MATERI BIOLOGI - Muh Khalifah Mustami (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2007)
One of the important tasks in teaching is assisting students to think. Synectics Model matched with Mind Maps are viewed necessary to be applied in the instruction in order to achieve the target.The research is an experiment research with pre-test post-test control group design. The results of analyses indicate that: (1) there is significance difference with the mean score of creative think ability, creative attitude, and mastery of biology materials due to difference of instruction model used, (2) there is no significant difference of mean score of creative attitude among the students who belong to the high and low achievement. (3) there is no interactional effect between the instructional model used with the students entry behavior towards creative thinking ability, creative attitude, and mastery of biology materials.